ANALYSIS OF THE LIBERALIZATION OF THE FIXED TELEPHONE COMMUNICATION MARKET IN LITHUANIA - Stanikūnas, Rimantas (Ekonomika, 2009)
This paper deals with the analysis of a relevant issue, regarding the liberalisation of the fixed telephone communication. The paper also deals with the characteristic features of monopoly markets, evaluates market power, both before liberalisation of fixed telephone communication and following the removal of monopoly powers. The paper includes an extensive discussion of the evaluation of barriers preventing entry in the market. It also determines the market power of Lietuvos telekomas (Teo LT AB) fixed telephone communication, based on various market concentration indicators. The purpose of the article is to present the analysis of the liberalization of the fixed telephone communication market in Lithuania and to reveal the inter-coherence of theoretical and practical elements of the liberalization.